2006
DOI: 10.1071/as05041
|View full text |Cite
|
Sign up to set email alerts
|

Saturn's Icy Moon Rhea: A Prediction for its Bulk Chemical Composition and Physical Structure at the Time of the Cassini Spacecraft First Flyby

Abstract: I report a model for the formation of Saturn's family of mid-sized icy moons to coincide with the first flypast of Rhea by the Cassini spacecraft on 2005 November 26. It is proposed that the moons had condensed from a concentric family of orbiting gas rings that were shed some 4.6610 9 yr ago by the proto-Saturnian (hereafter p-Sat) cloud. The p-Sat cloud is made up of gas and residual grains of the gas ring that was shed by the proto-Solar cloud (hereafter PSC) at Saturn's orbit. The bulk of the condensate wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…This would most likely also rule out the existence of a deep subsurface ocean that would have been conceivable if the satellite were differentiated and contained at least small amounts of ammonia (Hussmann et al, 2006). It was also suggested that a high abundance of ammonia ice in Rhea's interior may have prevented the formation of the ice-II phase in the central regions (Prentice, 2006). The formation of an ice-II core would be associated with a global contraction of the satellite that would have left its marks at the satellite's surface.…”
Section: Rheamentioning
confidence: 99%
“…This would most likely also rule out the existence of a deep subsurface ocean that would have been conceivable if the satellite were differentiated and contained at least small amounts of ammonia (Hussmann et al, 2006). It was also suggested that a high abundance of ammonia ice in Rhea's interior may have prevented the formation of the ice-II phase in the central regions (Prentice, 2006). The formation of an ice-II core would be associated with a global contraction of the satellite that would have left its marks at the satellite's surface.…”
Section: Rheamentioning
confidence: 99%
“…Prior to the Cassini flyby in Nov 2005, it was unclear if Rhea is differentiated and hence various possibilities had to be taken into account (Castillo-Rogez, 2006). It was also suggested that a high abundance of ammonia ice in Rhea's interior may have prevented the formation of the ice-II phase in the central regions (Prentice, 2006). The C 22 /J 2 ratio is consistent with hydrostatic equilibrium within the given error bounds (Iess et al, 2006).…”
Section: Rhea and Iapetusmentioning
confidence: 99%
“…The ammonia bearing compounds are absent on the surface but radar indicates an increase in ammonia with depth. Anyway, the total content of ammonia in Rhea is probably low (Ostro et al 2006, Prentice 2006.…”
Section: Introductionmentioning
confidence: 99%